2022
DOI: 10.1186/s12879-022-07479-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors associated with herpes zoster in England: a cross-sectional analysis of the Health Survey for England

Abstract: Background Herpes zoster (commonly called shingles) is caused by the reactivation of varicella zoster virus, and results in substantial morbidity. While the risk of zoster increases significantly with age and immunosuppression, relatively little is known about other risk factors for zoster. Moreover, much evidence to date stems from electronic healthcare or administrative data. Hence, the aim of this study was to explore potential risk factors for herpes zoster using survey data from a national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…The patients with herpes zoster in the present study had a mean age similar to that reported in other studies (54.9–57.1 years) [ 20 , 23 , 24 ], and there was a predominance in women, as found in other studies (55.5%–64.5%) [ 3 , 9 , 14 , 15 , 20 , 25 ]. Women were found to have a higher risk of presenting a first recurrence of herpes zoster, consistent with other reports [ 17 , 18 , 25 ]. Likewise, increasing age was a risk factor, consistent with other studies [ 17 , 18 , 25 ].…”
Section: Discussionsupporting
confidence: 89%
“…The patients with herpes zoster in the present study had a mean age similar to that reported in other studies (54.9–57.1 years) [ 20 , 23 , 24 ], and there was a predominance in women, as found in other studies (55.5%–64.5%) [ 3 , 9 , 14 , 15 , 20 , 25 ]. Women were found to have a higher risk of presenting a first recurrence of herpes zoster, consistent with other reports [ 17 , 18 , 25 ]. Likewise, increasing age was a risk factor, consistent with other studies [ 17 , 18 , 25 ].…”
Section: Discussionsupporting
confidence: 89%
“…3 Herpes zoster (HZ) is considered to be reactivated by a previous infection with VZV and nearly has the same transmission routes either by direct contact or by infected respiratory secretion. In a review by Thomas et al, 4 stated that the lifetime prevalence of HZ was 10%-30% and may rise to 50% in those over 85 years old; another cross-sectional study performed in England stated that the lifetime prevalence among English population was 12.6% for female and 10.3% for males 5 and the risk increased among those of white ethnicity and ex-smokers. 5 HZ is mainly presented by erythematous skin rash, which is very painful; this maculopapular rash is confined to one area of the skin called the dermatome and is usually present on one side of the body.…”
Section: Introductionmentioning
confidence: 99%
“…In a review by Thomas et al, 4 stated that the lifetime prevalence of HZ was 10%-30% and may rise to 50% in those over 85 years old; another cross-sectional study performed in England stated that the lifetime prevalence among English population was 12.6% for female and 10.3% for males 5 and the risk increased among those of white ethnicity and ex-smokers. 5 HZ is mainly presented by erythematous skin rash, which is very painful; this maculopapular rash is confined to one area of the skin called the dermatome and is usually present on one side of the body. 6 Some people reported a burning sensation in the dermatome before the appearance of the rash; they describe it as an electric sensation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations